A practical methodology for computer-aided design of custom 3D printable casts for wrist fractures - Buonamici, Francesco; Furferi, Rocco; Governi, Lapo; Lazzeri, Simone; McGreevy, Kathleen S.; Servi, Michaela; Talanti, Emiliano; Uccheddu, Francesca; Volpe, Yary (The Visual computer, 2020)
In recent years, breakthroughs in the fields of reverse engineering and additive manufacturing techniques have led to the development of innovative solutions for personalized medicine. 3D technologies are quickly becoming a new treatment concept that hinges on the ability to shape patient-specific devices. Among the wide spectrum of medical applications, the orthopaedic sector is experiencing the most benefits. Several studies proposed modelling procedures for patient-specific 3D-printed casts for wrist orthoses, for example. Unfortunately, the proposed approaches are not ready to be used directly in clinical practice since the design of these devices requires significant interaction among medical staff, reverse engineering experts, additive manufacturing specialists and CAD designers. This paper proposes a new practical methodology to produce 3D printable casts for wrist immobilization with the aim of overcoming these drawbacks. In particular, the idea is to realize an exhaustive system that can be used within a paediatric environment. It should provide both a fast and accurate dedicated scanning of the hand-wrist-arm district, along with a series of easy-to-use semi-automatic tools for the modelling of the medical device. The system was designed to be used directly by the clinical staff after a brief training. It was tested on a set of five case studies with the aim of proving its general reliability and identifying possible major flaws. Casts obtained using the proposed system were manufactured using a commercial 3D printer, and the device’s compliance with medical requirements was tested. Results showed that the designed casts were correctly generated by the medical staff without the need of involving engineers. Moreover, positive feedback was provided by the users involved in the experiment.